The Implementation of English Guessing Game to Students’ Speaking Skill at 8th Grade of MTsN Pademawu Pamekasan. - Zuhri, Muhammad Darrin (Universitas Madura, 2026)
The aim of this research to find of How is process the implementation of guessing game to student speaking skill in 8th grade of MTsN Pademawu Pamekasan. The approach to this research uses a qualitative research approach. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. Qualitative research is research that produces analytical procedures that do not use statistical analysis procedures or other data quantification methods in the form of words, images and not numbers. Therefore, research reports will contain data quotations to provide an overview of the presentation of the report. The use of guessing games can develop students' speaking skills. Because in the learning process students are required to actively speak, that is, students are able to answer descriptions on picture word cards, students' speaking skills will also increase. makes students interested in learning English, helps develop cognitive abilities and can train students' speaking skills teachers.Keyword: Implementation, Guessing Game, speaking skill